A rare case of early‐onset neonatal sepsis. Issue 3 (September 2014) - Chan, Eric; Mildenhall, Lindsay; Taylor, Susan
Abstract : Introduction: Capnocytophaga sputigena is a capnophilic Gram‐negative bacillus normally residing intra‐orally in humans, and may be associated with opportunistic infections in the immunocompromised. A case of early‐onset neonatal sepsis is described, which has only rarely been reported as a cause of premature birth and neonatal septicaemia. Case presentation: This case report focuses on the rare presentation of a microbe, Capnocytophaga sputigena, causing pre‐term labour, early neonatal septicaemia and maternal chorioamnionitis. To the best of our knowledge, it is the first case report of such a presentation in New Zealand. This case helps to demonstrate the contrast between the stormy clinical course in the newborn and the silent asymptomatic presentations in the mother. Conclusion: Capnocytophaga spp. normally reside in the human oral cavity and have been associated with the pathogenesis of periodontal disease. They have also been reported in wounds in humans inflicted by animal bites, and in a wide spectrum of opportunistic infections in the immunocompromised. Only rarely have Capnocytophaga spp. been attributed as a cause associated with pre‐term birth, early neonatal septicaemia or chorioamnionitis.